Oxford Studies in Experimental Philosophy Volume 3 2020
DOI: 10.1093/oso/9780198852407.003.0012
|View full text |Cite
|
Sign up to set email alerts
|

Intuitive Expertise and Irrelevant Options

Abstract: In the ‘push-dilemma,’ a train is about to run over several people and can only be stopped by pushing a heavy person onto the tracks. Most lay people and moral philosophers consider the ‘push-option,’ i.e., pushing the heavy person, as morally wrong. Peter Unger (1992, 1996) suggested that adding irrelevant options to the push-dilemma would overturn this intuition. This chapter tests Unger’s claim in an experiment with both lay people and expert moral philosophers. This allowed an investigation of the ‘experti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In Experiment 1A, we sought to replicate existing work on order effects in moral judgments of trolley dilemmas Wiegmann & Waldmann, 2014;Wiegmann et al, 2020). We used the standard Switch and Push paradigms.…”
Section: Experiments 1a: Asymmetrical Order Effectmentioning
confidence: 99%
“…In Experiment 1A, we sought to replicate existing work on order effects in moral judgments of trolley dilemmas Wiegmann & Waldmann, 2014;Wiegmann et al, 2020). We used the standard Switch and Push paradigms.…”
Section: Experiments 1a: Asymmetrical Order Effectmentioning
confidence: 99%
“…It goes without saying that philosophers have genuine expertise in some domains: among others, they know more about the history of philosophy, and they have acquired distinct skills, from close, accurate reading to clarity and precision in argumentation. On the other hand, philosophers appear to suffer from the biases that impact lay people's judgments (Machery 2012;Horvath and Wiegmann 2016, Forthcoming;Wiegmann et al 2020): order effects, framing effects, etc., influence some of their judgments (particularly, the judgments about thought experiments) to the same extent as lay people's.…”
Section: Two Objectionsmentioning
confidence: 99%
“…A fourth dimension is the number of options, and more precisely the presence of a third option (3O). Past research has shown that introducing a third option in a moral dilemma can dramatically switch participants’ moral preferences (Wiegmann et al, 2020). In the context of moral dilemmas including AVs, Bigman and Gray (2020) have shown that introducing a third option allowing the AV to make a decision at random drastically reduced the relevance of certain factors such as age, gender or social status.…”
Section: Introductionmentioning
confidence: 99%